PENGARUH PERBESARAN LUAS ELEKTRODA TERHADAP TEGANGAN TEMBUS PADA DIELEKTRIK UDARA MENGGUNAKAN SUMBER TEGANGAN TINGGI AC - Angkasa, Aulia; Dhofir, Moch.; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
Breakdown voltage events often occur as a failure of the insulation system in electrical equipment, whether in liquid dielectrics in the form of oil or gas dielectrics in the form of air. An example of a breakdown voltage phenomenon in an electric power system such as a substation is failure (breakdown) between two contacts/conductors of a circuit breaker (CB) or transformer in a substation. The difference in the dimensions of the area of the two contacts/conductors of the circuit breaker influences the distribution of the electric field around the contacts so that it can influence the probability of a breakdown voltage occurring between the two contacts of the circuit breaker which can be likened to two electrodes with different dimensions. In calculatingthe probability of a breakdown voltage occurring, the Gaussian distribution function can be used based on the law of electrode area enlargement (enlargement law). Therefore, this research will describe the effect of increasing the electrode area on the characteristics of the breakdown voltage using an AC (Alternating Current) voltage source. The research method used is by taking data through testing breakdown voltage and leakage current at the High Voltage Laboratory, Department of Electrical Engineering, Faculty of Engineering, Brawijaya University and simulating the distribution of the electric field at each variation of electrode magnification a, 2a, 3a, 4a, and 5a using FEMM 4.2 software. The results obtained in this research are the influence of increasing the electrode area on the characteristics of the breakdown voltage and leakage current. Keywords — Breakdown voltage; Leakage current; Probability; Enlargement law; Electric field